An activity-theoretic approach to intention estimation - Jipp, Meike; Bartolein, Christian; Badreddin, Essameddin (IFAC Proceedings Volumes, 2008)
Traditional powered wheelchair control is especially for severely disabled people cognitively and physically demanding due to the high number of input commands necessary. An intention estimation behaviour, which considers the cognitive processes of the actor, is discussed as one way in order to significantly reduce the number of required input commands. For this purpose, a continuum of, from other researchers discussed modes of human behaviour is introduced as well as cognitive processes underlying this continuum of human behaviour. A study conducted with wheelchair users confirms major assumptions of the theory and allows drawing implications for realizing an intention estimation behavior considering the cognitive processes of the actors.